[tex]\underline{\underline{\large\bf{Solution:-}}}\\[/tex]
[tex]\longrightarrow[/tex]Since angle X and Y have a sum of 159
[tex]\implies \bf Y + X= 159 \_\_\_\_(1) [/tex]
[tex]\longrightarrow[/tex]Since X is 43 degrees smaller than Y , so subtracting X from Y would give 43 , therefore equation will be written as -
[tex]\implies \bf Y - X = 43 \_\_\_\_(2) [/tex]
Adding Equation (1) and (2)
[tex]\begin{gathered}\\\implies\quad \sf Y+X+Y-X = 159+43 \\\end{gathered} [/tex]
[tex]\begin{gathered}\\\implies\quad \sf Y+Y + X-X = 202 \\\end{gathered} [/tex]
[tex]\begin{gathered}\\\implies\quad \sf 2Y = 202 \\\end{gathered} [/tex]
[tex]\begin{gathered}\\\implies\quad \sf Y = \frac{202}{2} \\\end{gathered} [/tex]
[tex]\begin{gathered}\\\implies\quad \boxed{\sf {Y = 101 }} \\\end{gathered} [/tex]
Putting Y in eq (1)
[tex]\begin{gathered}\\\implies\quad \sf X + 101 = 153 \\\end{gathered} [/tex]
[tex]\begin{gathered}\\\implies\quad \sf X = 153-101 \\\end{gathered} [/tex]
[tex]\begin{gathered}\\\implies\quad \boxed{\sf{ X = 52 }}\\\end{gathered} [/tex]